The Effect of Entrepreneurial-STEM (E-STEM) Learning on High School Students’ Problem-Solving Skills - Saraesa, Muhammad Nur Azzura; Aa Juhanda; Gina Nuranti; Rohayati (BIOEDUKASI: Jurnal Biologi dan Pembelajarannya, 2025)
This study aimed to determine the effect of the Entrepreneurial-STEM (E-STEM) learning model on students’ problem-solving skills in the topic of environmental change in Grade 10 biology. The E-STEM model integrates science, technology, engineering, and mathematics with entrepreneurial practices through contextual project-based learning. A quasi-experimental design using a Non-Equivalent Control Group was employed in two classes at a public senior high school in Sukabumi City, involving 31 students in the experimental group and 29 students in the control group. Research instruments included an essay test based on Polya’s problem-solving indicators, a student response questionnaire, and a learning implementation observation sheet. Data analysis involved normality and homogeneity tests, hypothesis testing (Mann-Whitney), normalized gain (N-Gain), and triangulation of quantitative and qualitative data. The results indicated a significant difference in posttest scores between the experimental and control groups, with the experimental group achieving a higher N-Gain (0.55, medium category) compared to the control group (0.24, low category). The most notable improvements occurred in the planning and evaluating solution indicators. Learning implementation reached 91.70% and student responses averaged 80.32%, both classified as very good. These findings suggest that the E-STEM model has a positive and significant effect on enhancing students’ structured and meaningful problem-solving skills. This study provides contextual empirical evidence for Indonesian biology education and highlights the need for further research with broader samples and longer implementation periods to strengthen the generalizability of the findings.